The Changes on Scale-Up Agriculture Business Transformation Process in Rural Area - Devi Maulida Rahmah; Fahmi Rizal; Sarinarulita Rosalinda (Journal of Industrial and Information Technology in Agriculture, 2017)
This study aims to identify the changes in Scale-up Business Transformation Process in PT Malabar Kopi Indonesia. PT Malabar Kopi Indonesia is the largest coffee processing business unit in West Java, established in 2005. Initially, this coffee business was categorized to household-scale coffee processing business (Small enterprise scale) and currently the company has become a coffee processing business unit that exports coffee to various countries. The development of this business is eligible to be identify the business changes occured. This study was conducted through field observation and deep interview. The data were analyzed through historical analysis. Through historical analysis approach, all details in innovation process conducted by PT Malabar Kopi will be explained.The results show that the changes on scale-up transformation process is divided into 4 terms, namely product changes, process changes, technological changes, and organizational changes. Product changes occurred four times along the business established. Initially, the company produced cherry bean as the main product on 2005. Changes occurred due to the company's desire to meet the market demand and increase value-added of products on 2009, when started producing green bean and roasted bean. In 2014 they started producing instant coffee and increased the production quantity of Green bean and roasted bean to meet the international market through exporting activity. The Process changes occurred 4 times, it closely related to the product changes. The changes from wet process to dry process occurred on 20014 due to the company target which focused to export market. The change also occurred on 2017 when the dry process moved to the natural process due to the domestic market become the targeted on this year. Shortly, the process chanced occurred based on the market will be targeted. The Technological changes helped the company to get the good quality and quantity of product. In term of the organizational changes, it become the basic change to get the market expansion. Especially in 2014, in the initially formed of company that categorized into small and medium scale enterprises moved to large scale enterprise. Marked by the transformation into a limited liability company (PT). The changes that occur have an impact on the networking opportunity and develop a broader business. Here is the historical change of business form.